Changes of physical and chemical parameters of organic and conventional carrots during storage - Csambalik, László; Hollinetz, Sámuel Andor; Divéky-Ertsey, Anna (Analecta Technica Szegedinensia, 2023)
In industrialised countries, around 670 million tonnes of food are lost every year, much of it still fit for human consumption. Due to the special nutrient management of organic farming, root vegetables have a higher dry matter content and a lower nitrate content, which also affects their shelf-life. The effect of storage under domestic conditions was investigated in our experiments on organic and conventional carrot lots. It was found that packaged organic carrots in a 4°C environment showed the longest shelf life, lowest nitrate content and weight loss during household storage. The results of the experiment may contribute to lower food waste through changes in consumer habits.